EXTERNAL AND INTERNAL EGG QUALITY CHARACTERISTICS OF INDIGENOUS SIRUVIDAI, ASEEL AND WHITE LEGHORN CHICKENS - D. Gandhimathi; P. Muthusamy; R. Richard churchil; K. Thilak Pon Jawahar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to evaluate external and internal egg quality characters of three chicken breeds/ ecotypes namely, indigenous Siruvidai, TANUVAS Aseel and White Leghorn. A total of 180 eggs (120 eggs from Siruvidai chicken, 30 eggs from TANUVAS Aseel and 30 eggs from White Leghorn) were subjected to this study. The weight, length, width and surface area of White Leghorn eggs were significantly (P<0.05) higher than those of TANUVAS Aseel and indigenous Siruvidai chicken. Shape index was found to be significantly (P<0.05 higher in Siruvidai chicken eggs compared to that of TANUVAS Aseel and White Leghorn. Among the internal egg qualities, the height and width of albumen and albumen index were significantly (P<0.05) higher in White Leghorn chicken eggs compared to that of TANUVAS Aseel and Siruvidai chicken. Yolk height and yolk index of three breeds showed no significant difference among breeds. Yolk width was significantly (P<0.05) higher in TANUVAS Aseel compared to that of Siruvidai chicken. Yolk colour was significantly (P<0.05) higher in TANUVAS Aseel and Siruvidai chicken compared to that of White Leghorn. Shell thickness was significantly (P<0.05) higher in TANUVAS Aseel and White Leghorn as compared to Siruvidai chicken. Haugh unit was significantly (P<0.05) higher in White Leghorn compared to TANUVAS Aseel and Siruvidai chicken. The results revealed that the egg quality characters like egg weight, egg length, egg width, shape index, surface area, albumen height, albumen index, shell thickness and Haugh unit of indigenous Siruvidai chicken is different from other indigenous breed like Aseel and exotic breed like White Leghorn.